Strategi Transformasi Holding BUMN DEFEND ID dalam Percepatan Kemandirian Alat Peralatan Pertahanan dan Keamanan untuk Mendukung Pertahanan Nasional - Priyono, Andri Bayu (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
Independence of defense and security equipment (Alpalhankam) is a strategic priority for Indonesia to reduce dependence on imports and strengthen national sovereignty. This article examines the transformation carried out by the State-Owned Enterprises Holding Defend ID—consisting of PT Pindad, PT Dirgantara Indonesia, PT PAL, PT LEN, and PT Dahana—in accelerating defense independence through technological integration and innovation. This study uses a comparative method by comparing the DEFEND ID strategy with countries that have achieved defense independence, such as Turkey and South Korea. The results of the study show that DEFEND ID has successfully increased the production capacity of defense equipment, such as the Anoa 6x6 combat vehicle, and increased exports by 15% in 2023. The synergy between SOEs has also contributed to cost efficiency of up to 20% in the last three years. However, there are significant challenges in technology transfer, human resource development (HR), and dependence on the state budget. These challenges include limitations in negotiating offset agreements, a shortage of high-tech experts, and the need for financing diversification. The study recommends accelerating technology transfer through stronger offset policies, developing high-tech-based training centers, and increasing access to international financing for strategic projects. With this strategy, DEFEND ID can strengthen its contribution in supporting national sovereignty and security, while increasing Indonesia's competitiveness at the global level. This article makes an important contribution to discussions related to national defense independence.